A Microfluidic‐Based Model for Spatially Constrained Culture of Intestinal Microbiota. (9th October 2018) - Pajoumshariati, Seyed Ramin; Azizi, Morteza; Zhang, Shiying; Dogan, Belgin; Simpson, Kenneth W.; Abbaspourrad, Alireza
Abstract: Perturbation of the microbiome is implicated in the pathogenesis of many human ailments, including inflammatory bowel diseases such as Crohn's disease (CD). Recapitulating the microbiome associated with health and disease necessitates controlling the composition of multiple bacterial species. This is difficult to achieve in vitro due to the overgrowth of bacterial species over time. Here, a microfluidic‐based model incorporating bacteria‐embedded hydrogel microfibers for the coculture of human enteric bacteria is introduced. Employing bacterial species and strains associated with CD, it is shown that the hydrogel‐based bacteria‐embedded microfiber model is physically and mechanically robust, and tunable. Metabolite analysis of the medium in both mono‐ and coculture revealed the interfiber exchange of soluble mediators and their impact on the growth of different bacterial species. This novel approach should enhance the ability to decipher contact‐independent cross‐talk within the polymicrobial intestinal luminal environment, and its impact on the intestinal epithelium. Abstract : To unravel complex polymicrobial interactions linked to inflammatory bowel diseases it is necessary to recapitulate the intestinal microbiome in health and disease. Current in vitro models are confounded by the relative overgrowth of resident enteric species and pathosymbionts. Here, a novel microfluidic‐approach to embed viable bacteria in microfibers is introduced, enabling coculture of human enteric microbes in vitro.